Layered Simple Hydroxides Functionalized by Fluorene‐Phosphonic Acids: Synthesis, Interface Theoretical Insights, and Magnetoelectric Effect. (11th September 2017) - Evrard, Quentin; Chaker, Ziyad; Roger, Mélissa; Sevrain, Charlotte M.; Delahaye, Emilie; Gallart, Mathieu; Gilliot, Pierre; Leuvrey, Cédric; Rueff, Jean‐Michel; Rabu, Pierre; Massobrio, Carlo; Boero, Mauro; et al.
Abstract: Copper‐ and cobalt‐based layered simple hydroxides (LSH) are successfully functionalized by a series of fluorene mono‐ and diphosphonic acids, using anionic exchange reactions and a preintercalation strategy. The lateral functionalization of the fluorene moieties has only little impact on the overall structure of the obtained layered hybrid materials but it influences the organization of the molecules within the interlamellar spacing. For bulky fluorene (9, 9‐dioctyl derivative), luminescence is preserved when inserted into copper and cobalt hydroxydes, whereas it is completely quenched for the other fluorenes. Detailed characterization of the internal structure and chemical bonding properties for copper‐ and cobalt‐based hybrids is performed via ancillary experimental techniques. For the copper‐based LSH class, for which more elusive findings are found, first‐principles molecular dynamics simulations unravel the fundamental stabilizing role of the H‐bonding network promoted within the local environments of the fluorene mono‐ and diphosphonic acids. The cobalt series of compounds constitute a new class of hybrid magnets, with ordering temperatures ranging from 11.8 to 17.8 K and show a clear magnetoelectric effect. This effect appears above a threshold magnetic field, which is null below the magnetic ordering temperature, and it persists in the paramagnetic regime till about 110 K. Abstract : Copper‐ and cobalt‐layered simple hydroxides can be functionalized by a series of fluorene phosphonic acids. X‐ray diffraction and first‐principles molecular dynamics underline the role of water molecules at the organic–inorganic interface in the copper analogues. The cobalt analogues present a ferrimagnetic ordering at T C ranging from 11.8 to 17.8 K and a rare magnetoelectric effect, which extends until 110 K.